Can we utilise upper tropospherical winds for tracking storms in the Bay of Bengal ? - BAGHARE , M. M.; DATTA, R. K. (MAUSAM, 1970)
In this study, the tracks of eleven cyclonic storms in the Bay of Bengal have been examined with a view to finding out if upper winds alone in the vicinity of the centre of cyclonic storms, could be useful in prognosticating the movement of these storms. By smoothened analysis of zonal (u) and meridional (v) components of the upper winds over various stations, the wind velocity for standard levels have been computed corresponding to the sea level position of the storm. The winds thus computed for various levels have been discussed from the point of view of their operational use in forecasting the movement of Bay storms. The limitations of such computations have also been brought out.